Formal institution building in financialized capitalism: the case of repo markets - Leon Wansleben (Theory and Society, 2020)
Money markets are at the heart of financialized capitalism, as those markets that provide the funding liquidity needed for credit creation and leveraged trading. How have these markets evolved, grown, and become critical for larger financial flows? To answer this question, I distinguish an early period of financial globalization marked by regulatory arbitrage, offshoring, deregulation, and informal trading practices from a period of regime-consolidation marked by formal institutionalization. Concentrating on repo markets as the key funding sources for market-based banking, I demonstrate that new institutional arrangements for these markets were initiated by private sector associations, but supported and authorized by public authorities. Bond trader groups codified new contractual arrangements and these were validated via reforms of bankruptcy codes and changes in central banks' policy frameworks in the United States and European Union. Through these modifications and re-articulations in institutional conditions, transactions and large exposures on money markets became routine affairs—for shadow banking actors like money market funds as well as for commercial banks. The article concludes by discussing the continuity of regime-consolidation efforts after the transatlantic financial crisis and hypothesizes that they reveal “neo-patrimonial” features.
Keywords: 300; Central banks; Financialization; Legal aspects of finance; Market infrastructures; Money markets; Repo